2020
DOI: 10.14740/jmc3543
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Bladder Endometriosis in a Patient With Previous Cesarean Sections

Abstract: Urological endometriosis is rare and accounts for approximately 1% of women with endometriosis. The pathophysiology of bladder endometriosis may be divided into two different causes, namely primary and secondary. The primary form occurs spontaneously and manifests in a form of a generalized pelvic disease whereas the secondary form is thought to be iatrogenic and typically occurs after pelvic surgery such as Cesarean section or hysterectomy. We present a case report on a patient presenting with an invasive bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that the assessment of urinary bladder deformities relies on the use of techniques such as uroscopy, magnetic resonance imaging. The research emphasizes the role of cystoscopy in diagnosing these deformities and even the possibility of taking samples for con rmation [1]. In our patient, upon conducting some laboratory tests, the following ndings were observed: Urine analysis: the eld is lled with red blood cells, Creatinine: 1 and INR: 2.5.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Studies have shown that the assessment of urinary bladder deformities relies on the use of techniques such as uroscopy, magnetic resonance imaging. The research emphasizes the role of cystoscopy in diagnosing these deformities and even the possibility of taking samples for con rmation [1]. In our patient, upon conducting some laboratory tests, the following ndings were observed: Urine analysis: the eld is lled with red blood cells, Creatinine: 1 and INR: 2.5.…”
Section: Discussionmentioning
confidence: 65%
“…In a study conducted by Vercellini and colleagues, they observed bladder abnormalities in only two out of 40 women, noting that these two women did not experience any symptoms. The absence of periodic symptoms for pelvic uterine abnormalities may be related to the use of Mirena [1]. In the case of our patient, a 37-year-old married woman with a child, she has been suffering from recurrent urinary tract infections for a year, experiencing burning during urination and pelvic pain for three years.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations